Generations of reformers in the Polish people’s republic and their intellectual heritage - Morawski, Wojciech (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
The drive towards reforms in the area of economic policy is permanent. The need of reforms is a practically never abandoned subject. The only exceptions tend to be periods when the status quo is accepted, and it is its consolidation that is being discussed. Things did not look any different in the times of the Polish People’s Republic (PPR). The rhythm of subsequent reform attempts determined the chronology of the development of the situation. The author set himself two goals: chronological ordering and typologisation of reform efforts in the PPR and presentation of the continuation of certain ways of thinking at the turn of the year 1989. Typologisation was assumed to concern ways of thinking rather than specific people and thus, it is not a biographic guide to reform circles.